(untitled) (Journal of Enam Medical College, 2016)
Background: Eczema is one of the important causes of public health problem. So, we conducted a study to assess the socio-demographic characteristics (age, sex, occupation, socio-economic condition, site of lesion, diabetes status etc) and to find out their relationship with the complicated eczema. Objective: The objective of the study was to find out the eczema cases attending in Department of Dermatology of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) Hospital and to identify the surface complications of eczema and the occurrence of eczema among the diabetic patients of BIRDEM Hospital. Materials and Methods: This cross-sectional study was carried out among the outdoor diabetic patients attending the Department of Dermatology of BIRDEM Hospital, Dhaka, Bangladesh during the period of 1st September to 31st November, 2014. Results: A total of 600 patients were interviewed. Of them, 60% were female and 40% were male. Among them, majority (29.17%) were in the age group of 4049 years. Most of the subjects (66.67%) were service holders. Majority of the subjects (61.67%) were from low socio-economic status. In majority cases (41.67%) lesions were in hand and in 33.33% in legs. Diabetes was uncontrolled in 76.67% cases and only 15% controlled it and 8.33% controlled strictly. Conclusion: Factors like occupation, diabetes status etc. were found associated with high occurrence of eczema. J Enam Med Col 2016; 6(2): 93-96